Pengaruh Shift Kerja Terhadap Stress Kerja pada 5 Orang Karyawan PT. Asam Jawa Kota Pinang - Batubara, Inggrid Mentari; Aritonang, Alifia Octaviani; Batubara, Layla Hanum; Salianto, Salianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Occupational Safety and Health Branch (2008) explains that optimizing work shift arrangements can help reduce the potential health impact on employees. Shifts involve a variety of work schedules and patterns, and their arrangement must take into account a number of factors, including the length of the shift or the number of hours worked per shift, number of team members, work breaks, rotation period or speed, and shift time. The purpose of this research is to find out how the influence of shift work on the stress level of PT. Tamarind Employee in the City of Pinang. To find out whether there is a relationship between work shift variables and work stress of PT. Tamarind City of Pinang, this study uses a qualitative methodology. This study involved 114 participants. This study shows that although morning shift workers do not experience high levels of stress, night shift workers do, which lowers their overall level of productivity. evening and night. Worker performance, health and psychosocial problems are the subject of the complaint. Except for the night shift workers who complained of a lack of focus at work due to poor quality, there was no difference in physical complaints experienced by morning shift workers and night shift workers in terms of body parts complaints. Sleep. so that the impact of shift work on employee work stress can be observed. Keywords: work stress, shift work